1973
DOI: 10.1017/s0022112073000236
|View full text |Cite
|
Sign up to set email alerts
|

Vortex shedding from bluff bodies in a shear flow

Abstract: Experiments are described in which the vortex shedding from a bluff body and the base pressure coefficient have been measured in a shear flow. It is shown that the shedding breaks down into a number of spanwise cells in each of which the frequency is constant. The division between the cells is thought to be marked by a longitudinal vortex in the stream direction and this is supported by evidence from experiments where a longitudinal vortex was generated in an otherwise uniform flow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
27
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(32 citation statements)
references
References 5 publications
5
27
0
Order By: Relevance
“…The size and stability of such cells have some subtle di!erences with similar structures encountered in stationary cylinders, as synchronization (lock-in) and multi-mode response compete directly with frequency mismatching along the span. The latter is the primary reason for the cell formation in either sheared #ow or uniform #ow past tapered cylinders (Maull & Young 1973;Noack et al 1991;Williamson 1992). The results from the experimental work suggest that the size of the cells is proportional to the amplitude of vibration and inversely proportional to the shear parameter .…”
Section: Introductionmentioning
confidence: 86%
“…The size and stability of such cells have some subtle di!erences with similar structures encountered in stationary cylinders, as synchronization (lock-in) and multi-mode response compete directly with frequency mismatching along the span. The latter is the primary reason for the cell formation in either sheared #ow or uniform #ow past tapered cylinders (Maull & Young 1973;Noack et al 1991;Williamson 1992). The results from the experimental work suggest that the size of the cells is proportional to the amplitude of vibration and inversely proportional to the shear parameter .…”
Section: Introductionmentioning
confidence: 86%
“…bodies have been extensively investigated (Zdravkovich 1997). Maull & Young (1973) found that the shedding phenomenon was greatly a!ected by the complexity of the oncoming stream, e.g., a blu! body in shear #ow would lead to vortex shedding occurring in spanwise cells.…”
Section: Introductionmentioning
confidence: 99%
“…These studies have shown that a cellular shedding pattern has been observed along with a spanwise variation of the base pressure. Maull & Young (1973), in one of the earliest studies on the subject, noticed the spanwise variation of base pressure across the cellular wake structures in a linear shear #ow past an airfoil-shaped body with a #at trailing edge. Mair and Stansby (1975) conducted essentially an extension of the Maull and Young study by performing similar experiments on relatively slender cylinders.…”
Section: Introductionmentioning
confidence: 99%